The Composition of Plants In Nepenthes Spp Community in Customary Forest of Lingkat Lake Kerinci - Susanti, Try Susanti; Kencanawati, Indah (Proceedings of the International Conference on Green Technology, 2018)
Nepenthes is a carniforous plant which has a unique shape, size and color of pitcher which makes it is popular as an exotic plant/decorative plant. However, the forest degradation and exploitation of Nepenthes Spp for economic purposes make the existence of natural habitats of Nepenthes Spp are increasingly threatened every year. So that, it is so important to do the research about composition of plant in the Nepenthes Spp community in customary forest of Lingkat Lake Kerinci. The research aimed to sort the species of Nepenthes spp and the species of plants in the community, as well as the important value and diversity of plants species index. The data was collected with the point intercept method, by putting 100 units of sampling, in the form of point intercept sampling framework with a distance 2 meters per sampling unit. The length of sampling unit (sampling framework) was about 1 meter with 10 touch points, the distance among the touch points were 10 cm. Therefore, the numbers of touch points in sampling site was 1000. The result of the research found that there were 3 species of Nepenthes Spp, they were: Nepenthes ampullaria Jack, Nepenthes mirabilis (Lour) Druce dan Nepenthes gracilis Korth. As many as 18 families recorded of 26 species of plants presented in the community of Nepenthes Spp. The highest impotance value was obtained by Nepenthes ampullaria Jack 21.23%, followed by Davalia repens(l.f) Kuhn 11.68% dan Nephrolepis hirsuta (C.Forst) 11.23%. The index of species diversity were low (1.649)